An appeal to khatibs and masjid authorities - Hasan, Md. Mahmudul (Human Assistance & Development International (HADI), 2024)
This essay mentions some topics that khatibs can choose while preparing their Friday khutbahs. There are many other down-to-earth issues—such as irresponsible use of social media—that they can consider while selecting the topics of their Friday addresses. I also believe that masjid authorities or management committee members have a role to play in addressing matters of topic selection for khutbahs.